Tree species diversity and economic value of a watershed forest in Ulu Muda Forest Reserve, Kedah - Ibrahim, Faridah Hanum; Simin, Miskon; Abd. Ghani, Awang Noor (Universiti Putra Malaysia Press, 1999)
Data on plant diversity are fundamental in the sustainable management of a forest. A study was conducted for a watershed forest, Ulu muda Forest Reserve, Kedah, with the objectives of determining tree species diversity and its economic value based on stumpage value. Results showed that there are 1072 trees with 92 species in 72 genera and 34 families in 1.2 hectare or 893 trees and 77 species per hectare. The most abundant species is Polyalthia rumphii while the largest families in terms of stem number are Annonaceae, Euphorbiaceae and Myrtaceae. About 3.25% of 2830 tree species in Peninsular Malaysia are found in this area. The stumpage value of tree species diversity of this forest is RM 41,445.30 per hectare. The stumpage value of trees below cutting limit is RM 1,863.98 per hectare while that ofupper cutting limit is RM 39,581.32 per hectare. Trees of diameter class >=60cm dbh contributed nearly 80% of the total stumpage value.